Preparation method of electromagnetic shielding fabric with bionic leaf-shaped layered structure

Through the preparation method of bionic leaf-like layered structure, combined with the synergistic effect of MXene and CuNWs, a high-performance electromagnetic shielding fabric is formed, which solves the problem of insufficient performance of existing electromagnetic shielding fabrics and achieves efficient electromagnetic shielding and multi-functional performance integration. .

CN119352285APending Publication Date: 2025-01-24SICHUAN UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411600010.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The existing electromagnetic shielding fabrics have insufficient performance in harsh environments and complex application scenarios, and the total electromagnetic shielding performance of MXene electromagnetic shielding fabrics cannot meet the commercial requirements, and the functions are single, and the performance is insufficient.

Method used

Using the preparation method of bionic leaf-like layered structure, the electromagnetic shielding fabric with bionic leaf-like layered structure was obtained by synthesizing MXene and CuNWs, adjusting the CuNWs loading concentration to form an electromagnetic shielding fabric loaded with MXene and CuNWs, and through PFOTES hydrophobic treatment. (MXene/CuNW0.96@SCF).

Benefits of technology

It has achieved high-efficiency electromagnetic shielding performance. The electromagnetic shielding efficiency is as high as 53.22dB, which can shield 99.9995% of electromagnetic waves. It has multi-mode heating, infrared stealth and self-cleaning properties. It is suitable for electromagnetic protective clothing for civilian, military and special groups.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119352285A_ABST
    Figure CN119352285A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of electromagnetic shielding fabric with a bionic leaf-shaped layered structure, which comprises the following steps: 1) etching an Al layer in Ti3AlC2 by adopting a LiF / HCl system, and performing ultrasonic stripping to obtain MXene nanosheets; (2) copper chloride is used as a precursor, oleylamine is used as an end-capping reagent, L-ascorbic acid is used as a reducing agent, and copper nanowire (CuNWs) dispersion liquid is prepared through a coprecipitation method; and (3) fixing the cleaned and dried cotton fabric on a vacuum filter, adding the CuNWs dispersion liquid and the MXene dispersion liquid in batches, carrying out alternate circulating vacuum suction filtration, and carrying out vacuum drying. And finally, carrying out hydrophobic modification by using 1H, 1H, 2H, 2H-perfluorooctyltriethoxysilane, and drying to obtain the electromagnetic shielding fabric with the bionic leaf-shaped layered structure. The bottleneck problem that an MXene electromagnetic shielding fabric is single in function and insufficient in performance is solved, the electromagnetic shielding fabric which is excellent in EMI shielding, dual-drive heating, infrared stealth, hydrophobic and flame-retardant is obtained through a conductive network formed through cooperation of CuNWs and MXene, and the electromagnetic shielding fabric is expected to be used as civil and military electromagnetic protective clothing and electromagnetic protective clothing for special crowds.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of new materials, and in particular to a method for preparing a bionic leaf-shaped layered structure electromagnetic shielding fabric. Background Art

[0002] The rapid development of electronic devices has brought great convenience to human life, but the electromagnetic interference and radiation generated seriously affect the normal operation of electronic devices and even threaten human health. The development of high-performance and reliable EMI shielding materials is highly favored in the fields of human health protection and military operations. Electromagnetic shielding fabrics have many attractive characteristics such as electromagnetic shielding function and deformable and cuttable fabric substrates. Compared with materials such as films, foams and aerogels, they are in line with the development trend of wearable. However, electromagnetic shielding fabrics with only shielding performance can no longer meet the harsh environmental climate and complex or changeable application scenarios. Realizing multimodal heating of EMI shielding fabrics indoors and outdoors to ensure the concealment of targets in military operations is of great significance for military and civilian electromagnetic shielding, thermal management and stealth applications. Photothermal and Joule heating have been used as complementary solutions to improve thermal comfort in cold climates. This dual-drive heating mode can also play an effective auxiliary role in bringing low-temperature targets close to background temperatures in high-temperature environments such as deserts, thereby avoiding detection and identification of targets by infrared detectors. Therefore, it is urgent to develop multifunctional EMI shielding fabrics that integrate thermal management and infrared stealth to meet complex practical application needs.

[0003] Transition metal carbonitride (MXene) is one of the most promising candidates for advanced EMI shielding materials, with excellent conductivity, good mechanical properties and high specific surface area. Based on the localized surface plasmon resonance effect of MXene, it has a strong absorption effect on the solar spectrum and a high photothermal conversion rate. And based on its low infrared emissivity, MXene can also exhibit infrared stealth behavior. Compared with other conductive nanomaterials such as carbon nanotubes, graphene and acetylene black, MXene's hydrophilicity and dispersibility in water are more suitable for combination on flexible fabric substrates. However, MXene alone cannot be assembled into an excellent interconnected conductive network on fabrics, and there is still a problem of shielding efficiency amplification limitation, which limits its performance and single function.

[0004] The Chinese invention patent with publication number CN112663323A discloses a MXene electromagnetic shielding fabric and its preparation method and application. The invention immerses a plasma-pretreated flexible fabric substrate in a MXene dispersion, dries it, and condenses it in a CO 2 However, heat treatment will cause the exposed Ti layer on the outermost surface of MXene to undergo oxidation reaction with the surface oxygen-containing groups to generate TiO 2, which in turn affects the inherent material properties of MXene, resulting in the overall electromagnetic shielding effectiveness of the invented MXene electromagnetic shielding fabric failing to meet commercial requirements (20dB).

[0005] A Chinese invention patent with publication number CN111501326A discloses a multifunctional wearable polymer / MXene composite fabric heater and a preparation method thereof. When preparing the polymer / MXene composite fabric heater, the invention adopts an impregnation method to directly bond MXene to the surface of the fabric substrate. Although the solution impregnation composite method can comprehensively and quickly composite MXene to the surface of the fabric substrate, this method of directly bonding MXene to the fabric substrate will make the MXene easily oxidized and fall off, reducing the electromagnetic shielding effect and the photothermal conversion efficiency.

[0006] In addition, the original hydrophilicity of MXene electromagnetic shielding fabrics will cause the material to be contaminated by acid, alkali and salt solutions, and even the functional layer will be severely corroded, resulting in a significant decrease in material performance, making MXene electromagnetic shielding fabrics challenging in terms of durability and solvent resistance; secondly, the low mechanical properties of MXene materials lead to a decrease in electromagnetic shielding performance in practical applications, especially in deformation states or under high-intensity ultrasound, thereby limiting their application in wearable devices and smart textiles.

[0007] Therefore, it is necessary to provide a method for preparing a bionic leaf-shaped layered structure electromagnetic shielding fabric to achieve multifunctional integration such as multimodal heating, infrared stealth and self-cleaning performance, and solve the above technical problems. Summary of the invention

[0008] The present invention overcomes the shortcomings of the prior art, provides a method for preparing a bionic leaf-shaped layered structure electromagnetic shielding fabric, solves the problem of low shielding effectiveness of electromagnetic shielding fabrics in the prior art, and solves the bottleneck problem of single function and insufficient performance of MXene electromagnetic shielding fabrics, and provides a composite fabric (MXene / CuNW 0.96 @SCF) has high photothermal conversion, Joule heating, hydrophobic self-cleaning, flame retardant, corrosion resistance and mechanical resistance while ensuring high electromagnetic shielding effectiveness, making it suitable for electromagnetic protective clothing for civilian, military and special groups.

[0009] To achieve the above object, the technical solution adopted by the present invention is: a method for preparing a bionic leaf-shaped layered structure electromagnetic shielding fabric, comprising the following steps:

[0010] S1. Add lithium fluoride to the hydrochloric acid solution to convert the MAX phase Ti 3 AlC 2Add to the solution, stir to react, etch the aluminum layer, and form a reactant; centrifuge the reactant and wash it with water for multiple times, take the supernatant and add water and ultrasound to peel off the multilayer MXene; centrifuge the reactant again to obtain a supernatant MXene dispersion;

[0011] S2, CuCl 2 ·2H 2 O is dissolved in water, and ethanol, oleylamine, and L-ascorbic acid are added to the copper chloride solution in sequence; the reaction is carried out in an oil bath, and the red precipitate is washed with anhydrous ethanol, and then collected and redispersed in anhydrous ethanol to obtain a copper nanowire (CuNWs) dispersion;

[0012] S3, cutting the cotton fabric, ultrasonically cleaning it with ethanol and NaOH aqueous solution, and drying it;

[0013] S4. Fix the cotton fabric washed and dried in S3 on a vacuum filter, add CuNWs dispersion and MXene dispersion in batches for alternating cycle vacuum filtration, and vacuum dry to obtain electromagnetic shielding fabric loaded with CuNWs and MXene.

[0014] S5. After drying, the S4 electromagnetic shielding fabric is immersed in an ethanol solution of 1H, 1H, 2H, 2H-perfluorooctyltriethoxysilane, and dried to obtain an electromagnetic shielding fabric with a bionic leaf-like layered structure.

[0015] In a preferred embodiment of the present invention, in S1, the concentration of hydrochloric acid is 7-11 mol / L, Ti 3 AlC 2 The mass ratio of lithium fluoride to hydrochloric acid is 1:1-2:6-8; the stirring reaction temperature is 35-40°C, and the stirring reaction time is 24-36h;

[0016] In a preferred embodiment of the present invention, in S1, when the reactant is centrifuged and washed with water, the centrifugal speed is 8000-10000 r / min, the centrifugal time is 5-15 min, the centrifugal end point is until the pH of the dispersion is close to 5-7, the ultrasonic power is 50-100%, and the ultrasonic time is 0.5-1.5 h; when the reactant is centrifuged again, the centrifugal speed is 3000-4000 r / min, the centrifugal time is 20-40 min, the supernatant is taken and diluted with water to obtain a MXene dispersion with a concentration of 3-7 mg / ml;

[0017] In a preferred embodiment of the present invention, in S2, the CuCl 2 ·2H 2 O and L-ascorbic acid in a molar ratio of 1:1, CuCl 2 ·2H 2 The mass ratio of O and oleylamine is 1:1-3, and the volume ratio of ethanol and oleylamine is 6-10:1;

[0018] In a preferred embodiment of the present invention, in S2, the oil bath temperature is 80-90°C, the reaction time is 4-12h; the centrifugal speed is 8000-10000r / min, and the centrifugal time is 5-15min;

[0019] In a preferred embodiment of the present invention, in S3, the cotton fabric is cut into a circular shape with a diameter of 5 to 7 cm, the drying temperature is 50 to 80° C., the concentration of the NaOH aqueous solution is 10 wt %;

[0020] In a preferred embodiment of the present invention, in S4, the concentration of the MXene dispersion is 3-7 mg / mL, and the concentration of the CuNWs dispersion is 0.56-1.06 mg / mL;

[0021] In a preferred embodiment of the present invention, in said S5, the vacuum drying temperature is 35-45°C;

[0022] In a preferred embodiment of the present invention, in S5, the concentration of 1H,1H,2H,2H-perfluorooctyltriethoxysilane ethanol solution is 1%, the immersion time is 2-4h, and the vacuum drying temperature is 35-45°C.

[0023] The present invention solves the defects existing in the background technology and has the following beneficial effects:

[0024] (1) The present invention provides a method for preparing a bionic leaf-shaped hierarchical electromagnetic shielding fabric. By synthesizing MXene and CuNWs and adjusting the different CuNWs loading concentrations, a series of multifunctional high-performance electromagnetic shielding fabrics loaded with MXene and CuNWs are obtained. After PFOTES hydrophobic treatment, an electromagnetic shielding fabric with a bionic leaf-shaped hierarchical structure (MXene / CuNW) is obtained. 0.96 @SCF). Through the synergistic effect of multi-scale conductive materials including two-dimensional MXene nanosheets (mesophyll) and one-dimensional CuNWs (veins), a continuous, stable, and interlaced conductive network is formed. The conductive path established thereby effectively improves the electromagnetic shielding performance and dual-driven heating performance. Compared with cotton fabrics and fabrics loaded with only MXene and CuNWs (CF, MXene@CF, and CuNWs@CF), composite fabrics loaded with MXene and CuNWs and covered with a hydrophobic coating (MXene / CuNW 0.96 @SCF) has an electromagnetic shielding effectiveness of up to 53.22dB, which can shield 99.9995% of electromagnetic waves, far exceeding the expected value (20dB) required for commercial applications.

[0025] (2) The present invention compares the effects of the presence or absence of a hydrophobic coating on the dual-driven heating performance of the composite fabric loaded with MXene and CuNWs. Since the interlaced conductive network of MXene nanosheets and CuNWs jointly promotes the absorption and conversion of light, the hydrophobic coated fabric MXene / CuNWs 0.96 The saturation temperature of @SCF can be as high as 98.6°C, and it still has excellent and stable light-to-heat conversion capabilities under repeated solar heating and cooling cycles and severe cold climates; and Joule heating is used as a thermal compensation solution to expand the application scenarios of the electromagnetic shielding fabric of the present invention. MXene / CuNW 0.96 @SCF exhibits efficient and stable Joule heating performance (the saturation temperature is 81.4°C at 1.5V), and the saturation temperature is positively linearly related to the square of the voltage, which is highly consistent with Joule's law, further proving the active controllability of its Joule heating performance. It can be used as an adjustable conductive heat source supply device according to actual use needs. In addition, based on the low infrared emissivity characteristics of MXene, it can effectively prevent the diffusion of thermal radiation and also give electromagnetic shielding fabrics excellent infrared stealth performance.

[0026] (3) The present invention uses the micro-nano structure formed by low surface energy materials PFOTES and CuNWs and MXene to give MXene / CuNWs@SCF roughness, effectively reducing the contact area between water and solids, weakening the adhesion between the fabric surface and the droplets, so that the electromagnetic shielding fabric in the present invention also has hydrophobic properties, and realizes the self-cleaning of the fabric. It has anti-pollution ability against pollution sources such as dyes, and has excellent EMI shielding performance stability in acid, alkali and salt solutions, as well as under the action of bending and ultrasonic mechanical forces, reflecting that the hydrophobic coating makes the fabric exhibit good corrosion resistance and mechanical resistance. In addition, the conductive coating involved in the present invention plays a positive role in the flame retardancy of the fabric. After combustion, CuNWs are converted into copper nanoparticles and adhere to the surface of the fabric fiber; the early transition metal compounds in MXene effectively hinder the release of gas and smoke, and are oxidized to TiO 2 The particles promote the formation of residual carbon, which acts as a physical isolation barrier between the condensed phase and the gas phase. These particles may help fill the gaps to form a denser protective layer, thereby slowing down the degree of combustion. Based on the above excellent performance of the present invention, MXene / CuNWs@SCF is expected to be used as electromagnetic protective clothing for civilian, military and special groups in multiple scenarios and multiple needs, so as to expand the application scope of CuNWs in research fields such as electromagnetic shielding, photothermal, and Joule heating. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art are briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For those of ordinary skill in the art, other drawings can be obtained based on these drawings without creative work.

[0028] Figure 1 TEM image of MXene (a) and SEM image of CuNWs (b);

[0029] Figure 2 The scanning electron microscope images and EDS element distribution images of electromagnetic shielding fabrics obtained at different CuNWs loading concentrations prepared in Examples 2 to 4 of the present invention;

[0030] Figure 3 is a scanning electron microscope image and an EDS element distribution map of the bionic leaf-shaped layered structure electromagnetic shielding fabric prepared in Example 1 of the present invention;

[0031] Figure 4 It is a graph of the total electromagnetic shielding effectiveness of different electromagnetic shielding fabrics prepared in Examples 1 to 4 of the present invention, Comparative Examples 1 and 2;

[0032] Figure 5 is the electromagnetic shielding performance retention rate of the electromagnetic shielding fabrics prepared with or without hydrophobic post-treatment in Example 1 and Example 2 of the present invention under solutions of different properties and different mechanical forces;

[0033] Figure 6 Infrared thermal imaging images of electromagnetic shielding fabrics with or without hydrophobic post-treatment prepared in Example 1 and Example 2 of the present invention under different light intensities and different heating voltages, and linear relationship diagrams between the saturation temperature of the two fabrics and the square of the voltage;

[0034] Figure 7 The infrared stealth effect diagram of the cotton fabric after washing of the present invention, Example 1 and Example 2 on the palm of a human body and the radiation temperature difference diagram of the cotton fabric after washing compared with the radiation temperature of Example 1 and Example 2 at different hot stage temperatures;

[0035] Figure 8 The contact angle diagrams (a) and (b) of Example 1, Example 2, Comparative Example 1 and Comparative Example 2 of the present invention, MXene / CuNW 0.96 Self-cleaning effect of @SCF on gardenia yellow dye (b), and MXene / CuNW 0.96 @Color change diagram of SCF and gardenia yellow dye (c);

[0036] Fig. 9The cotton fabric (a) of the present invention and the bionic leaf-shaped hierarchical structure hydrophobic electromagnetic shielding fabric MXene / CuNW of Example 1 are 0.96 @SCF flame retardant effect diagram (b). DETAILED DESCRIPTION

[0037] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0038] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein. Therefore, the protection scope of the present invention is not limited to the specific embodiments disclosed below.

[0039] It should be noted that the raw materials, equipment and reagents used in the present invention can be purchased from the market or obtained through the preparation methods of existing technologies.

[0040] A preparation method of a bionic leaf-shaped layered structure electromagnetic shielding fabric comprises the following steps:

[0041] S1. Add lithium fluoride to the hydrochloric acid solution to convert the MAX phase Ti 3 AlC 2 Add to the solution, stir to react, etch the aluminum layer, and form a reactant; centrifuge the reactant and wash it with water for multiple times, take the supernatant and add water and ultrasound to peel off the multilayer MXene; centrifuge the reactant again to obtain a supernatant MXene dispersion;

[0042] S2, CuCl 2 ·2H 2 O is dissolved in water, and ethanol, oleylamine, and L-ascorbic acid are added to the copper chloride solution in sequence; the reaction is carried out in an oil bath, and the red precipitate is washed by centrifugation and anhydrous ethanol, and then collected and redispersed in anhydrous ethanol to obtain a CuNWs dispersion;

[0043] S3, cutting the cotton fabric, ultrasonically cleaning it with ethanol and NaOH aqueous solution, and drying it;

[0044] S4. Fix the cotton fabric washed and dried in S3 on a vacuum filter, add CuNWs dispersion and MXene dispersion in batches for alternating cycle vacuum filtration, and vacuum dry to obtain electromagnetic shielding fabric loaded with CuNWs and MXene.

[0045] S5. Immerse the S4 electromagnetic shielding fabric in an ethanol solution of 1H, 1H, 2H, 2H-perfluorooctyltriethoxysilane and dry it to obtain an electromagnetic shielding fabric with a bionic leaf-like layered structure.

[0046] In some specific embodiments, in S1, the hydrochloric acid concentration is 7-11 mol / L, Ti 3 AlC 2 The mass ratio of lithium fluoride to hydrochloric acid is 1:1-2:6-8; the stirring reaction temperature is 35-40°C, and the stirring reaction time is 24-36h;

[0047] In some specific embodiments, in S1, when the reactant is centrifuged and washed with water, the centrifugal speed is 8000-10000 r / min, the centrifugal time is 5-15 min, the centrifugal end point is until the pH of the dispersion is close to 5-7, the ultrasonic power is 50-100%, and the ultrasonic time is 0.5-1.5 h; when the reactant is centrifuged again, the centrifugal speed is 3000-4000 r / min, the centrifugal time is 20-40 min, the supernatant is taken and diluted with water to obtain a MXene dispersion with a concentration of 3-7 mg / mL;

[0048] In some specific embodiments, in S2, the CuCl 2 ·2H 2 O and L-ascorbic acid in a molar ratio of 1:1, CuCl 2 ·2H 2 The mass ratio of O to oleylamine is 1:1-3, and the volume ratio of ethanol to oleylamine is 6-10:1.

[0049] In some specific embodiments, in S2, the oil bath temperature is 80-90°C, the reaction time is 4-12h; the centrifugal speed is 8000-10000r / min, and the centrifugal time is 5-15min.

[0050] In some specific embodiments, in S3, the cotton fabric is cut into a circular shape with a diameter of 5 to 7 cm, the drying temperature is 50 to 80° C., and the concentration of the NaOH aqueous solution is 10 wt %.

[0051] In some specific embodiments, in S4, the concentration of the MXene dispersion is 3 to 7 mg / mL, and the concentration of the CuNWs dispersion is 0.56 to 1.06 mg / mL.

[0052] In some specific embodiments, in S5, the vacuum drying temperature is 35-45°C.

[0053] In some specific embodiments, in S5, the concentration of 1H,1H,2H,2H-perfluorooctyltriethoxysilane ethanol solution is 1%, the immersion time is 2-4h, and the vacuum drying temperature is 35-45°C.

[0054] Example 1

[0055] This embodiment provides a preparation and application technology of a hydrophobic electromagnetic shielding fabric with a bionic leaf-like layered structure:

[0056] 1) MXene etching: 3.2 g lithium fluoride was weighed and added to 40 mL 9 mol / L hydrochloric acid solution at room temperature, and then 2 g Ti 200 was slowly added to the MXene phase. 3 AlC 2 Add it to the solution, stir the reaction at 40°C to etch the aluminum layer; then, centrifuge the product (8000r / min, 10min) and wash it with water several times until the pH of the dispersion is close to 6. After taking the supernatant, add water and ultrasound (power 80%, ultrasound 1h) to peel off the multilayer MXene; then centrifuge at 3500r / min for 30min to obtain the supernatant MXene dispersion.

[0057] 2) CuNWs synthesis: Weigh CuCl 2 ·2H 2 O is dissolved in water, and then ethanol, oleylamine, and L-ascorbic acid are added to the copper chloride solution in sequence, and then stirred thoroughly. 2 ·2H 2 The molar ratio of O and L-ascorbic acid is 1:1, and the volume ratio of ethanol and oleylamine is 6-10:1; the reaction container is then immersed in an 85°C oil bath for 12 hours, and when it cools to room temperature, it is centrifuged (8000r / min, 10min), the red precipitate is washed with anhydrous ethanol, and the precipitate is collected and redispersed in anhydrous ethanol to obtain a copper nanowire (CuNWs) dispersion.

[0058] 3) Biomimetic leaf-like hierarchical structure hydrophobic electromagnetic shielding fabric (MXene / CuNW 0.96 @SCF) Preparation: The cotton fabric was cut into a 6 cm diameter circle, and ultrasonically cleaned with ethanol and 10 wt% NaOH aqueous solution to remove oil stains and other impurities and dried; then the cotton fabric was fixed on a vacuum filter, and 0.96 mg / mL CuNWs dispersion and 5 mg / mL MXene dispersion were added in batches for alternating cycle vacuum filtration, and then placed in a 40°C vacuum drying oven for 40 minutes. The obtained fabric loaded with MXene and CuNWs was immersed in an ethanol solution of 1% 1H, 1H, 2H, 2H-perfluorooctyl triethoxysilane for 3 hours, taken out and placed in a 40°C vacuum drying oven to dry, and a hydrophobic electromagnetic shielding fabric MXene / CuNW with a bionic leaf-like hierarchical structure loaded with MXene and CuNWs was obtained.0.96 @SCF.

[0059] Example 2

[0060] This embodiment is basically the same as embodiment 1, except that: in step 3), the cotton fabric is cut into a circle with a diameter of 6 cm, ultrasonically cleaned with ethanol and 10 wt% NaOH aqueous solution, respectively, to remove oil stains and other impurities, and then dried; then the cotton fabric is fixed on a vacuum filter, 0.96 mg / mL CuNWs dispersion and 5 mg / mL MXene dispersion are added in portions for alternating cycle vacuum filtration, and after the filtration is completed, it is placed in a vacuum drying oven at 40°C and dried for 20 minutes to obtain MXene / CuNWs 0.96 @CF. This embodiment does not carry out the subsequent hydrophobic post-treatment (immersion in ethanol solution of 1H, 1H, 2H, 2H-perfluorooctyltriethoxysilane and vacuum drying process).

[0061] Example 3

[0062] This embodiment is basically the same as embodiment 1, except that: in step 3), the cotton fabric is cut into a circle with a diameter of 6 cm, and ultrasonically cleaned with ethanol and 10 wt% NaOH aqueous solution to remove oil stains and other impurities and dried; then the cotton fabric is fixed on a vacuum filter, 0.76 mg / mL CuNWs dispersion and 5 mg / mL MXene dispersion are added in portions for alternating cycle vacuum filtration, and after the filtration is completed, it is placed in a vacuum drying oven at 40°C and dried for 20 minutes to obtain MXene / CuNWs 0.76 @CF, no subsequent hydrophobic post-treatment (1H, 1H, 2H, 2H ~ perfluorooctyltriethoxysilane ethanol solution immersion and vacuum drying process) was performed.

[0063] Example 4

[0064] This embodiment is basically the same as embodiment 1, except that: in step 3), the cotton fabric is cut into a circle with a diameter of 6 cm, and ultrasonically cleaned with ethanol and 10 wt% NaOH aqueous solution to remove oil stains and other impurities and dried; then the cotton fabric is fixed on a vacuum filter, 0.56 mg / mL CuNWs dispersion and 5 mg / mL MXene dispersion are added in portions for alternating cycle vacuum filtration, and after the filtration is completed, it is placed in a vacuum drying oven at 40°C for 20 minutes to obtain MXene / CuNWs 0.56 @CF, no subsequent hydrophobic post-treatment (immersion in 1% 1H,1H,2H,2H-perfluorooctyltriethoxysilane ethanol solution and vacuum drying process) was performed.

[0065] Example 5

[0066] This embodiment is basically the same as embodiment 1, except that: the cotton fabric is cut into a circle with a diameter of 5 to 7 cm, and ultrasonically cleaned with ethanol and 10 wt% NaOH aqueous solution to remove oil stains and other impurities, and then dried; then the cotton fabric is fixed on a vacuum filter, 0.76 mg / mL CuNWs dispersion and 5 mg / mL MXene dispersion are added in batches for alternating cycle vacuum filtration, and after the filtration, it is placed in a vacuum drying oven at 40°C for 20 min; the obtained fabric loaded with MXene and CuNWs is immersed in an ethanol solution of 1% 1H,1H,2H,2H-perfluorooctyltriethoxysilane for 3 h, taken out and placed in a vacuum drying oven at 40°C for drying.

[0067] Example 6

[0068] This embodiment is basically the same as embodiment 1, except that: the cotton fabric is cut into a circle with a diameter of 5 to 7 cm, and ultrasonically cleaned with ethanol and 10 wt% NaOH aqueous solution to remove oil stains and other impurities, and then dried; then the cotton fabric is fixed on a vacuum filter, 0.56 mg / mL CuNWs dispersion and 5 mg / mL MXene dispersion are added in batches for alternating cycle vacuum filtration, and after the filtration, it is placed in a vacuum drying oven at 40°C for 20 min; the obtained fabric loaded with MXene and CuNWs is immersed in an ethanol solution of 1% 1H,1H,2H,2H-perfluorooctyltriethoxysilane for 3 h, taken out and placed in a vacuum drying oven at 40°C for drying.

[0069] Example 7

[0070] This embodiment is basically the same as embodiment 1, except that: the cotton fabric is cut into a circle with a diameter of 5 to 7 cm, and ultrasonically cleaned with ethanol and 10 wt% NaOH aqueous solution to remove oil stains and other impurities, and then dried; then the cotton fabric is fixed on a vacuum filter, 1.06 mg / mL CuNWs dispersion and 5 mg / mL MXene dispersion are added in batches for alternating cycle vacuum filtration, and after the filtration, it is placed in a vacuum drying oven at 40°C for 20 min; the obtained fabric loaded with MXene and CuNWs is immersed in an ethanol solution of 1% 1H,1H,2H,2H-perfluorooctyltriethoxysilane for 3 h, taken out and placed in a vacuum drying oven at 40°C for drying.

[0071] Comparative Example 1

[0072] This comparative example is basically the same as Example 1, except that: there is no CuNWs synthesis in step 2); in step 3), the cotton fabric is cut into a circle with a diameter of 6 cm, ultrasonically cleaned with ethanol and 10 wt% NaOH aqueous solution respectively to remove oil stains and other impurities and dried; then the cleaned cotton fabric is fixed on a vacuum filter, 5 mg / mL MXene dispersion is added in portions for cyclic vacuum filtration, and after the filtration, the fabric is placed in a vacuum drying oven at 40°C to dry to obtain MXene@CF, without subsequent hydrophobic post-treatment (immersion in 1% 1H,1H,2H,2H-perfluorooctyltriethoxysilane ethanol solution and vacuum drying process).

[0073] Comparative Example 2

[0074] This comparative example is basically the same as Example 1, except that: there is no MXene synthesis in step 1); in step 3), the cotton fabric is cut into a circle with a diameter of 6 cm, ultrasonically cleaned with ethanol and 10 wt% NaOH aqueous solution, respectively, to remove oil stains and other impurities and dried; then the cleaned cotton fabric is fixed on a vacuum filter, 0.96 mg / mL CuNWs dispersion is added in portions for cyclic vacuum filtration, and after the filtration, the fabric is placed in a vacuum drying oven at 40°C to dry, and CuNWs are obtained. 0.96 @CF, no subsequent hydrophobic post-treatment (1H, 1H, 2H, 2H ~ perfluorooctyltriethoxysilane ethanol solution immersion and vacuum drying process) was performed.

[0075] In order to verify the successful acquisition of the electromagnetic shielding fabrics in Examples 1 to 4, Figure 1 Shown are TEM images of MXene (a) and SEM images of CuNWs (b); Figure 2 The scanning electron microscope images and EDS element distribution diagrams of electromagnetic shielding fabrics obtained at different CuNWs loading concentrations prepared in Examples 2 to 4 of the present invention; Figure 3 The scanning electron microscope image and EDS element distribution map of the bionic leaf-shaped layered structure electromagnetic shielding fabric prepared in Example 1 of the present invention are shown; Figure 4 The total electromagnetic shielding effectiveness (SE) of different electromagnetic shielding fabrics prepared in Examples 1 to 4, Comparative Examples 1 and 2 of the present invention is shown. T ) Figure; Average electromagnetic shielding effectiveness (reflection loss SE) of electromagnetic shielding fabrics prepared in Examples 1 to 7 of the present invention R , absorption loss SE A And the total shielding effectiveness SE T ) are summarized in Table 1; Figure 5 It shows the electromagnetic shielding performance retention rate of the electromagnetic shielding fabrics prepared with or without hydrophobic post-treatment in Example 1 and Example 2 of the present invention under different properties of solutions and different mechanical forces; Figure 6Shown are infrared thermal imaging images of electromagnetic shielding fabrics with or without hydrophobic post-treatment prepared in Example 1 and Example 2 of the present invention under different light intensities and different heating voltages, as well as two linear relationship diagrams of saturation temperature and the square of applied voltage; Figure 7 The infrared stealth effect diagram of the cotton fabric after washing of the present invention, Example 1 and Example 2 on the palm of a human body and the radiation temperature difference diagram of the cotton fabric after washing compared with the radiation temperature of Example 1 and Example 2 at different hot stage temperatures are shown; Figure 8 The contact angle diagrams (a) and (b) of MXene / CuNW are shown in Example 1, Example 2, Comparative Example 1 and Comparative Example 2 of the present invention. 0.96 @SCF self-cleaning effect on gardenia yellow dye (b), MXene / CuNW 0.96 @Color change diagram of SCF and gardenia yellow dye (c); Fig. 9 The cotton fabric (a) of the present invention and the biomimetic leaf-like hierarchical structure hydrophobic electromagnetic shielding fabric MXene / CuNW of Example 1 are shown. 0.96 @SCF flame retardant effect diagram (b).

[0076] Table 1:

[0077]

[0078]

[0079] From Table 1, we can see that:

[0080] Example 1: The reflection loss is 11.52dB, the absorption loss is 41.70dB, and the total shielding effectiveness is the highest, which is 53.22dB; Example 2: Although the reflection loss is slightly lower than that of Example 1 (11.11dB), its absorption loss is higher (44.70dB), which improves the total shielding effectiveness to 55.81dB; Examples 3-4: As the CuNWs loading concentration decreases, the reflection loss and absorption loss both decrease, resulting in a decrease in the total shielding effectiveness; Examples 5-7: These examples vary in the CuNWs loading concentration and hydrophobic post-treatment, but overall they do not exceed the effectiveness of Example 1. It shows that under the MXene and CuNWs loading concentrations and process conditions of Example 1, the electromagnetic shielding performance is optimal.

[0081] from Figure 1 It can be seen that the LiF / HCl system selectively removes the MAX phase Ti 3 AlC 2 The Al layer in the CuNWs can be removed by ultrasonic stripping to prepare transparent MXene nanosheets. The CuNWs prepared by the co-precipitation method have a micron-scale long rod-like morphology and a high aspect ratio, which is conducive to forming an interconnected conductive network when mixed with MXene on cotton fabric.

[0082] Figure 2 The electromagnetic shielding fabric MXene / CuNW of Examples 2 to 4 is obtained at different CuNWs loading concentrations 0.96 @CF( Figure 2 c) MXene / CuNW 0.76 @CF( Figure 2 b) and MXene / CuNW 0.56 @CF( Figure 2 From the SEM image of a), it can be found that with the increase of CuNWs concentration, the surface of the original cotton fabric changes from smooth to rough, forming a more uniform coating. At the same time, more CuNWs are assembled onto the fabric surface together with MXene, and the MXene nanosheets are tightly and adaptively wrapped and bridged by CuNWs. Benefiting from the highly stable bonding between the components, a dual conductive network composed of 2DMXene and 1DCuNWs is constructed in the fabric. Interestingly, after hydrophobic treatment, their combination can form a bionic leaf-like hierarchical structure on cotton fabric, such as Figure 2 (c) and Figure 3 As shown in (a), CuNWs act as the conductive skeleton ("veins") and MXene nanosheets act as the "leiophyte", which closely connect and cover the individual CuNWs on the fabric substrate, generating a continuous conductive pathway for efficient electron transport. Figure 2 (d) and Figure 3 (b) MXene / CuNW 0.96 @CF and MXene / CuNW 0.96 The EDS spectra of @SCF all show that the corresponding elements are uniformly attached to the fabric matrix. 0.96 The good distribution of Si elements in @SCF indicates that PFOTES is successfully loaded. Therefore, EMI shielding fabric MXene / CuNW with biomimetic leaf-like hierarchical structure was prepared by vacuum-assisted filtration under the interaction of cotton fabric, MXene, CuNWs and PFOTES. 0.96 @SCF.

[0083] like Figure 4 As shown, by comparing cotton fabric, comparative example 1 (MXene@CF), comparative example 2 (CuNW 0.96 @CF), Example 1 (MXene / CuNW 0.96 @SCF), Example 2 (MXene / CuNW 0.96 @CF), Example 3 (MXene / CuNW 0.76 @CF) and Example 4 (MXene / CuNW 0.56 @CF) electromagnetic shielding fabric electromagnetic shielding effectiveness SE TIt was found that cotton fabrics showed negligible EMI shielding performance (2.7 dB) in the X-band (8.2-12.4 GHz) due to their electrical insulation properties, and electromagnetic waves can almost completely penetrate cotton fabrics. 0.96 @CF) EMI shielding SE T Lower (12.2dB), so CuNW 0.96 @CF does not reach the expected value (20dB) required for commercial applications. It is worth noting that the EMI shielding SET of cotton fabrics loaded with MXene and CuNWs exceeds 35dB due to their good electrical conductivity. Compared with cotton fabrics with only MXene or only CuNWs, with the addition of CuNWs, the EMI shielding SE T The value gradually increases, including MXene / CuNW 0.56 @CF,MXene / CuNW 0.76 @CF,MXene / CuNW 0.96 @CF, where MXene / CuNW 0.96 @CF's SE T Reaching 58.81dB, it can shield 99.9997% of electromagnetic waves, MXene / CuNW covered with hydrophobic coating 0.96 @SCF Although its SE T It dropped slightly, but still maintained at 53.22dB, which can shield 99.9995% of electromagnetic waves. This shows that low content of PFOTES has little effect on the continuity of the efficient conductive network composed of MXene and CuNWs. 0.96 @SCF can meet almost all shielding requirements of conventional electronic equipment.

[0084] The durability and solvent resistance of EMI shielding materials are very important performance indicators in practical applications. Whether the EMI shielding performance of the material can be maintained under liquid contamination and mechanical external force is also a problem worthy of attention in the design of EMI shielding materials. Figure 5 Example 2 (MXene / CuNW 0.96 @CF) and Example 1 (MXene / CuNW 0.96 @SCF) was immersed in hydrochloric acid solution (pH = 1), sodium hydroxide alkaline solution (pH = 13), sodium chloride aqueous solution (mass concentration 0.1wt%) and ethanol for 24 hours, and after repeated bending 500 times and ultrasonic damage for 30 minutes. The results show that except for the similar EMI shielding performance retention of the two fabrics under ethanol immersion conditions, after acid, alkali, salt solution, bending, and ultrasonic treatment, MXene / CuNW 0.96@SCF has a higher EMI shielding performance retention rate. On the one hand, the protective effect of the waterproof layer is conducive to improving the antioxidant capacity of the conductive filler, thereby slowing down the decline in EMI shielding performance; on the other hand, the hydrophobic coating can enhance the interaction between the conductive layer and the cotton fiber, protecting the conductive filler from falling off, so that it has excellent performance stability in the deformation state or under high-intensity ultrasound. MXene / CuNW 0.96 The high stability of EMI performance of @SCF in acidic environment can explain that extremely alkaline environment may cause hydrolysis or destruction of siloxane bonds, thus affecting the integrity and hydrophobicity of the coating.

[0085] Integrating sustainable solar heating and Joule heating into EMI shielding textiles is an effective way to achieve temperature regulation in multiple scenarios. Figure 6 (a) shows the infrared thermal imager testing the electromagnetic shielding fabrics of Example 1 and Example 2 at different light intensities (130, 160 and 190 mW / cm 2 ) surface saturation temperature, and found that MXene / CuNW 0.96 The saturation temperature of @SCF surface is slightly lower than that of MXene / CuNW 0.96 @CF, this is explained by the fact that the latter is not covered with a hydrophobic layer, which can more efficiently exert the good photothermal effect of MXene, but it can be foreseen that when the light intensity is lower than 160mW / cm 2 When MXene / CuNW 0.96 @SCF's heating temperature range can meet the requirements of outdoor solar heating. However, cotton fabrics have weak absorption of infrared light and are not suitable for outdoor solar heating. 2 The temperature slightly increased, and the saturation temperature was 38.18 °C, which was much lower than that of MXene / CuNW 0.96 @CF and MXene / CuNW 0.96 @SCF. At the same time, a cold platform was used to simulate a severe cold environment. When the temperature of the cold platform was ~25°C, the light intensity was 130mW / cm 2 MXene / CuNW within 3s 0.96 @CF and MXene / CuNW 0.96 The surface temperature of @SCF increased from ~1.9℃ and ~2.6℃ to 35.0℃ and 33.8℃, respectively, indicating that it still has excellent light-to-heat conversion performance in severe cold climates. Figure 6 (b) shows the surface saturation temperature of the electromagnetic shielding fabric in Example 1 and Example 2 under different voltages (0.5, 0.7, 1.0, 1.2, 1.5 V) tested by infrared thermal imaging. Since the electric heating equipment used for human hyperthermia usually operates in the temperature range of 40-60 °C, the MXene / CuNW 0.96 @CF and MXene / CuNW0.96 @SCF has excellent electrothermal conversion capabilities and can be used in other scenarios such as human hyperthermia by controlling the voltage according to actual usage requirements. Figure 6 (c) depicts that their saturation temperature has a positive linear relationship with the square of the voltage, which is highly consistent with Joule’s law, further demonstrating the active controllability of their Joule heating performance.

[0086] Electromagnetic interference shielding fabrics with infrared stealth properties are expected to play a key role in the fields of anti-surveillance and security protection. Figure 7 As shown in a, the radiation temperature of the electromagnetic shielding fabrics covered with Examples 1 and 2 on the palm of the human body is lower than the radiation temperature of the cotton fabric and the actual human skin surface temperature. 0.96 @CF and MXene / CuNW 0.96 @SCF were placed on a hot stage with different set temperatures (42.5℃, 50℃, 100℃ and 150℃) Figure 7 b), it was found that with the increase of the temperature of the heating platform, the temperature difference between the heated and cotton fabrics increased; these results reflect the low infrared emissivity characteristics of MXene, which can effectively prevent the diffusion of thermal radiation and give the electromagnetic shielding fabrics of Examples 1 and 2 infrared stealth properties.

[0087] Considering that MXene and copper nanowires are easily oxidized, in order to improve the MXene / CuNW 0.96 The durability of @CF ensures its performance stability during use. MXene / CuNW with a hydrophobic coating was obtained by the impregnation method. 0.96 @SCF. Figure 8 (a) The contact angles of water droplets contacting cotton fabric, electromagnetic shielding fabrics in Examples 1-2 and Comparative Examples 1-2 are compared. Cotton fabric is completely wettable by water, and MXene@CF also exhibits hydrophilicity. The contact angle of cotton fabric loaded with only CuNWs is 108.1°, which is due to the rough microstructure formed by random stacking of surface nanowires on the fabric surface, which exhibits hydrophobicity. This shows that the introduction of CuNWs is expected to increase the contact angle, and the MXene / CuNW 0.96 @CF has a higher contact angle than MXene@CF. 0.96 @CF was post-treated with PFOTES hydrophobicity, and its hydrophilic surface was converted into MXene / CuNW 0.96 @SCF hydrophobic surface, contact angle reaches 128.7°.

[0088] The hydrophobic property is conducive to the self-cleaning effect. When the gardenia yellow dye powder is used as a simulated pollution source in the MXene / CuNW 0.96When the @SCF surface was used, flowing water droplets with gardenia yellow powder attached to them could be easily rolled off the fabric by washing, indicating that it has anti-pollution ability.

[0089] also, Fig. 9 The cotton fabric and MXene / CuNW in Example 1 are compared. 0.96 @SCF flame retardant behavior, cotton fabric is more easily ignited when exposed to flames, and is engulfed by the rapidly spreading flames until it burns out, and the morphology of cotton fabric shrinks severely, while MXene / CuNW 0.96 The combustion transfer rate of @SCF is slower, and its morphology can be better maintained. On the one hand, after combustion, CuNWs are converted into copper nanoparticles and adhere to the surface of fabric fibers; on the other hand, the early transition metal compounds in MXene effectively hinder the release of gas and smoke, and are oxidized and converted into TiO2 particles, promoting the formation of residual carbon. This carbonized layer acts as an effective isolation barrier between the condensed phase and the gas phase. These particles fill the gaps to form a denser protective layer, thereby slowing down the degree of combustion.

[0090] The present invention synthesizes MXene and CuNWs, regulates different CuNWs loading concentrations, obtains a series of multifunctional high-performance electromagnetic shielding fabrics loaded with MXene and CuNWs, and obtains electromagnetic shielding fabrics with bionic leaf-like hierarchical structures (MXene / CuNW) through PFOTES hydrophobic treatment. 0.96 @SCF).

[0091] The conductive layer of the fabric is composed of 2DMXene nanosheets ("leaf flesh") and 1DCuNWs ("leaf veins") that are interlaced and interconnected. CuNWs act as a bridge and synergize with MXene to construct a continuous and highly stable dual conductive network, which is beneficial to enhance the electromagnetic shielding, electrothermal and photothermal conversion performance of the composite fabric. Finally, the composite fabric (MXene / CuNWs@SCF) with synergistic loading of MXene and CuNWs and covered with a hydrophobic coating has an electromagnetic shielding effectiveness of up to 53.2dB, which can shield 99.9995% of electromagnetic waves. It also has better EMI performance stability under liquid pollution or mechanical external force, and has excellent photothermal conversion performance under different light intensities (saturation temperature value up to 98.6°C), and can show excellent Joule heating performance at extremely low voltages (<1.5V). The radiation temperature of the fabric in the palm of the human body is lower than the radiation temperature covered by cotton fabric and the actual human skin surface temperature, and has excellent infrared stealth performance. Its hydrophobic properties make it anti-pollution, and the conductive materials of two dimensions are conducive to slowing down the burning degree of cotton fabrics. Therefore, the electromagnetic shielding fabric in the present invention is expected to be used as electromagnetic protective clothing for civilian, military and special populations under multiple scenarios and multiple needs, so as to expand the application scope of CuNWs in research fields such as electromagnetic shielding, photothermal, and Joule heating.

[0092] The above is based on the ideal embodiment of the present invention. Through the above description, it is obvious to those skilled in the art that the present invention is not limited to the details of the above exemplary embodiments, and the present invention can be implemented in other specific forms without departing from the spirit or basic characteristics of the present invention. Therefore, no matter from which point of view, the embodiments should be regarded as exemplary and non-restrictive. The scope of the present invention is limited by the attached claims rather than the above description, and it is intended to include all changes within the meaning and scope of the equivalent elements of the claims. Any figure mark in the claims should not be regarded as limiting the claims involved.

[0093] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A method for preparing a bionic leaf-shaped layered structure electromagnetic shielding fabric, characterized in that: The following steps are involved: S1. Add lithium fluoride to a hydrochloric acid solution, add MAX phase Ti3AlC2 to the solution, stir the reaction, etch the aluminum layer, and form a reactant; centrifuge the reactant and wash it with water for multiple times, take the supernatant and add water and ultrasound to peel off the multilayer MXene; centrifuge the reactant again to obtain a supernatant MXene dispersion; S2, dissolving CuCl2·2H2O in water, and sequentially adding ethanol, oleylamine, and L-ascorbic acid to the copper chloride solution; reacting in an oil bath, centrifuging, washing the red precipitate with anhydrous ethanol, and collecting and redispersing it in anhydrous ethanol to obtain a copper nanowire (CuNWs) dispersion; S3, cutting the cotton fabric, ultrasonically cleaning it with ethanol and NaOH aqueous solution, and drying it; S4. Fix the cotton fabric washed and dried in S3 on a vacuum filter, add CuNWs dispersion and MXene dispersion in batches for alternating cycle vacuum filtration, and vacuum dry to obtain electromagnetic shielding fabric loaded with CuNWs and MXene. S5. Immerse the S4 electromagnetic shielding fabric in an ethanol solution of 1H, 1H, 2H, 2H-perfluorooctyltriethoxysilane and dry it to obtain a bionic leaf-like hierarchical structure hydrophobic electromagnetic shielding fabric.

2. The method for preparing a bionic leaf-shaped layered structure electromagnetic shielding fabric according to claim 1, characterized in that: In S1, the concentration of hydrochloric acid is 7-11 mol / L, the mass ratio of Ti3AlC2, lithium fluoride and hydrochloric acid is 1:1-2:6-8; the stirring reaction temperature is 35-40°C, and the stirring reaction time is 24-36h.

3. The method for preparing a bionic leaf-shaped layered structure electromagnetic shielding fabric according to claim 1, characterized in that: In S1, the centrifugal speed is 8000-10000 r / min, the centrifugal time is 5-15 min, the centrifugal endpoint is until the pH of the dispersion is close to 5-7, the ultrasonic power is 50-100%, and the ultrasonic time is 0.5-1.5 h; when the reactant is centrifuged again, the centrifugal speed is 3000-4000 r / min, the centrifugal time is 20-40 min, the supernatant is taken and diluted with water to obtain a MXene dispersion with a concentration of 3-7 mg / mL.

4. The method for preparing a bionic leaf-shaped layered structure electromagnetic shielding fabric according to claim 1, characterized in that: In the S2, the molar ratio of CuCl2·2H2O to L-ascorbic acid is 1:1, the mass ratio of CuCl2·2H2O to oleylamine is 1:1-3, and the volume ratio of ethanol to oleylamine is 6-10:

1.

5. The method for preparing a bionic leaf-shaped layered structure electromagnetic shielding fabric according to claim 1, characterized in that: In S2, the oil bath temperature is 80-90°C, the reaction time is 4-12h; the centrifugal speed is 8000-10000r / min, and the centrifugal time is 5-15min.

6. The method for preparing a bionic leaf-shaped layered structure electromagnetic shielding fabric according to claim 1, characterized in that: In S3, the cotton fabric is cut into a circular shape with a diameter of 5 to 7 cm, and the drying temperature is 50 to 80° C.; the concentration of the NaOH aqueous solution is 10 wt %.

7. The method for preparing a bionic leaf-shaped layered structure electromagnetic shielding fabric according to claim 1, characterized in that: In S4, the concentration of the MXene dispersion is 3 to 7 mg / mL, and the concentration of the CuNWs dispersion is 0.56 to 1.06 mg / mL.

8. The method for preparing a bionic leaf-shaped layered structure electromagnetic shielding fabric according to claim 1, characterized in that: In the step S5, the vacuum drying temperature is 35 to 45°C.

9. The method for preparing a bionic leaf-shaped layered structure electromagnetic shielding fabric according to claim 1, characterized in that: In the S5, the concentration of 1H,1H,2H,2H-perfluorooctyl triethoxysilane ethanol solution is 1-2%, the immersion time is 2-4h, and the vacuum drying temperature is 35-45°C. 。

Citation Information

Patent Citations

  • Flexible high-strength MXene-based electromagnetic shielding composite film and preparation method thereof

    CN111809439A

  • Preparation method of CNF-MXene / silver nanowire porous composite film

    CN114369284A

  • Preparation method of flexible electromagnetic shielding fabric

    CN114855443A

  • Preparation method of CoFe2O4-coated MXene-AgNWs / CNF composite film

    CN117794210A

  • Preparation method and application of flexible multifunctional MXene / aramid nanofiber electromagnetic shielding film

    CN117887127A